2000
DOI: 10.1002/(sici)1099-0690(200005)2000:10<1945::aid-ejoc1945>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Behaviour of Non-Hydrolizable Lactose Analogues: The Thioglycoside, Carbaglycoside, and Carba-Iminoglycoside Cases

Abstract: The conformational behaviours of several nonhydrolizable lactose analogues, namely methyl α‐thiolactoside (1), methyl β‐carbalactoside (2) and methyl β‐carbaiminolactoside (3) have been studied using a combination of NMR spectroscopy (J and NOE data) and molecular mechanics calculations. Analogies and differences with the natural compounds have been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…[8,23] Due to the length and flexibility of the C-S bond, many conformations may be formed by rotation through the torsion angles φ (i.e., 1Ј-H-C-1Ј-S-C-4) and ψ (i.e., C-1Ј-S-C-4-4-H). [8,23] Due to the length and flexibility of the C-S bond, many conformations may be formed by rotation through the torsion angles φ (i.e., 1Ј-H-C-1Ј-S-C-4) and ψ (i.e., C-1Ј-S-C-4-4-H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,23] Due to the length and flexibility of the C-S bond, many conformations may be formed by rotation through the torsion angles φ (i.e., 1Ј-H-C-1Ј-S-C-4) and ψ (i.e., C-1Ј-S-C-4-4-H). [8,23] Due to the length and flexibility of the C-S bond, many conformations may be formed by rotation through the torsion angles φ (i.e., 1Ј-H-C-1Ј-S-C-4) and ψ (i.e., C-1Ј-S-C-4-4-H).…”
Section: Resultsmentioning
confidence: 99%
“…[8,23] Due to the length and flexibility of the C-S bond, many conformations may be formed by rotation through the torsion angles φ (i.e., 1Ј-H-C-1Ј-S-C-4) and ψ (i.e., C-1Ј-S-C-4-4-H). It has been reported that these conformations are preferred for the analogous thiodisaccharides, [8,23] and it is worth mentioning that they are stabilized by the favourable interactions of the sulfur lone-pair disposed anti to the C-1Ј-O-1Ј bond (the exoanomeric effect). [7,8,23] The NOESY spectrum of 4 showed interresidue NOE enhancements between 1Ј-H and 3-H, and between 1Ј-H and 4-H, which seems to confirm the respective syn φ/syn ψ and syn φ/anti ψ conformations around the thioglycosidic linkage.…”
Section: Resultsmentioning
confidence: 99%
“…The precise understanding of the parameters governing those changes is therefore essential to the design of new and more efficient therapeutic molecules. More specifically, the replacement of the exocyclic anomeric oxygen atom by a carbon atom leads to C ‐glycosides5 while replacement of the endocyclic one produces carbasugars 6. In both cases, when the aglycone is another glycoside, this transformation leads to non‐hydrolysable disaccharide analogues: C ‐disaccharides and carbadisaccharides (Figure 1).…”
Section: Second‐order Interaction Energy (E2 Kcal Mol−1) Between Donmentioning
confidence: 99%
“…S -Glycosides have been used as replacements for O -glycosides because of their similar conformational preferences about the anomeric bonds19 and because of the lower susceptibility of thioglycosides to enzymatic cleavage 20. Although a C-S bond is longer than a C-O bond, the C-S-C bond angle is significantly smaller than the C-O-C angle, which results in relatively small differences between the positions of the atoms along the glycosidic linkage.…”
mentioning
confidence: 99%